Bulk flow in the combined 2MTF and 6dFGSv surveys. Issue 4 (14th April 2018) - Qin, Fei; Howlett, Cullan; Staveley-Smith, Lister; Hong, Tao
Abstract: We create a combined sample of 10 904 late- and early-type galaxies from the 2MTF and 6dFGSv surveys in order to accurately measure bulk flow in the local Universe. Galaxies and groups of galaxies common between the two surveys are used to verify that the difference in zero-points is <0.02 dex. We introduce a maximum likelihood estimator (ηMLE) for bulk flow measurements that allows for more accurate measurement in the presence of non-Gaussian measurement errors. To calibrate out residual biases due to the subtle interaction of selection effects, Malmquist bias and anisotropic sky distribution, the estimator is tested on mock catalogues generated from 16 independent large-scale GiggleZ and SURFS simulations. The bulk flow of the local Universe using the combined data set, corresponding to a scale size of 40 h −1 Mpc, is 288 ± 24 km s −1 in the direction ( l, b ) = (296 ± 6°, 21 ± 5°). This is the most accurate bulk flow measurement to date, and the amplitude of the flow is consistent with the Λ cold dark matter expectation for similar size scales.